Quantz and his Versuch: Three Studies - Reilly, Edward R. (New York American Musicological Society Galaxy Music Corporation, 1971)
Studies dealing with Quantz's work as a composer, the dissemination of the Versuch in Germany and other European countries, and the musical and historical background of several topics dealt with in the treatise.
Appendix I: Quantz's Compositions in Manuscript: A Guide to Their Location; Appendix II: Eighteenth-Century Editions of Quantz's Music; Appendix III: Modern Editions of Quantz's Music; Bibliography: p. 164-173; Index
Keywords: Quantz, Johann Joachim -- 1697-1773; 18th Century (1701-1800); Method; Flute; Reception; Catalog; Berlin (Germany); Germany; Netherlands; United Kingdom; Italy